2010
DOI: 10.1128/jvi.01049-10
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Responses Are Required for Protection from Clinical Disease and for Virus Clearance in Severe Acute Respiratory Syndrome Coronavirus-Infected Mice

Abstract: A dysregulated innate immune response and exuberant cytokine/chemokine expression are believed to be critical factors in the pathogenesis of severe acute respiratory syndrome (SARS), caused by a coronavirus (SARS-CoV). However, we recently showed that inefficient immune activation and a poor virus-specific T cell response underlie severe disease in SARS-CoV-infected mice. Here, we extend these results to show that virus-specific T cells, in the absence of activation of the innate immune response, were sufficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
367
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 358 publications
(380 citation statements)
references
References 37 publications
13
367
0
Order By: Relevance
“…HLA-A*1101-, HLA-A*2402-, HLA-B*15-, and HLA-B*4001-restricted T-cell epitopes have also been defined, which can be used to detect T-cell immune responses among populations other than HLA-A2 Oh et al, 2011). Also, several H-2 d -, H-2 k -, and H-2 b -restricted CD4 þ T-cell and CD8 þ T-cell epitopes have been identified using different mouse strains, which are helpful for SARS-CoV-specific T-cell studies among these animal models and the development of vaccines (Zhao et al, , 2010aZhi et al, 2005). Given that all the CD4 þ T cell epitopes identified thus far are derived from the SARS-CoV S protein, further epitope discovery is still needed, especially in other structural proteins.…”
Section: Immunogenicity Of Sars-cov and T-cell Epitopesmentioning
confidence: 99%
See 3 more Smart Citations
“…HLA-A*1101-, HLA-A*2402-, HLA-B*15-, and HLA-B*4001-restricted T-cell epitopes have also been defined, which can be used to detect T-cell immune responses among populations other than HLA-A2 Oh et al, 2011). Also, several H-2 d -, H-2 k -, and H-2 b -restricted CD4 þ T-cell and CD8 þ T-cell epitopes have been identified using different mouse strains, which are helpful for SARS-CoV-specific T-cell studies among these animal models and the development of vaccines (Zhao et al, , 2010aZhi et al, 2005). Given that all the CD4 þ T cell epitopes identified thus far are derived from the SARS-CoV S protein, further epitope discovery is still needed, especially in other structural proteins.…”
Section: Immunogenicity Of Sars-cov and T-cell Epitopesmentioning
confidence: 99%
“…Mammalian CHO cells-expressing segments of the SARS-CoV S protein also induce potent T-cell immune responses and protection against the virus (Du et al, 2009b(Du et al, , 2010. Zhao and colleagues observed that enhanced virus-specific CD8 þ T-cells in mice by immunization with SARS-CoV peptide-pulsed dendritic cells also result in earlier virus clearance and increased survival (Zhao et al, 2010a). In a Phase I clinical trial, a single-plasmid DNA vaccine encoding the S protein was well tolerated and induced SARS-CoV-specific CD4 þ T-cell responses in all vaccinees, as well as CD8 þ T-cell responses in~20% of individuals (Martin et al, 2008).…”
Section: General Strategies For T-cell Based Vaccine Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…All these reports point to that it will be important to establishan appropriatecombination of vaccination route, vaccine vector andchoice of epitopes for each vaccine type.SARS vaccines thatgeneratea predominantly cellular or a predominantly humoral response, as well as therapeutic monoclonal antibodies, have been shown protectiveeffects in animal models. Therefore, what kind of responses are important for protection has not been clear (Subbarao et al, 2004;Zakhartchouk et al, 2005;Lin et al, 2007;See et al, 2008;Zhao and Perlman, 2010). Cameron et al (2012) have recently reported an analysis of transcripts expressed during SARS-CoV infection in vaccination and reinfectiontrials in ferrets (Cameron et al, 2012).…”
Section: Vaccines and Immunotherapy For Sars-covmentioning
confidence: 99%